Stakeholder Participation as a Means to Produce Morally Justified Environmental Decisions. Issue 1 (2nd January 2016) - Samuelsson, Lars; Rist, Lucy
Abstract: Stakeholder participation is an increasingly popular ingredient within environmental management and decision-making. While much has been written about its purported benefits, a question that has been largely neglected is whether decision-making informed through stakeholder participation is actually likely to yield decisions that are morally justified in their own right. Using moral methodology as a starting point, we argue that stakeholder participation in environmental decision-making (if adequately designed) may indeed be an appropriate means to produce morally justified decisions, the reason being that such participation may constitute an efficient way to satisfy the standard requirements on moral reasoning and moral justification. This finding also emphasizes the importance of identifying those settings most conducive to allowing different stakeholders to both challenge each other's arguments and to adopt each other's perspectives in order to make effective use of participation in environmental decision-making for the purpose of reaching morally justified decisions.